The role of mental health symptomology and quality of life in predicting referrals to special child and adolescent mental health services - Yoon, Yeosun (BMC Psychiatry, 2021)
BACKGROUND: Children and adolescents’ mental health problems have been largely assessed with conventional symptom scales, for example, Strengths and Difficulties Questionnaire (SDQ) given that it is one of the mostly widely used measures in specialist Child and Adolescent Mental Health Services (CAMHS). However, this emphasis on symptom scales might have missed some important features of the mental health challenges that children and young people experience including day to day functioning and life satisfaction aspect (i.e. qualify of life). METHOD: The study examined longitudinal association between a young person’s self-perceptions of quality of life and mental health difficulties and referral to specialist CAMHS service using a population cohort study (Targeted Mental Health in Schools service data) nested within a large-scale linkage between school (National Pupil Data base) and child mental health service administrative data (South London and Maudsley NHS Foundation Trust children and adolescent mental health services health records). Cox proportional hazard regression to estimate crude and adjusted hazard ratios (HRs) for the association between participant psychopathology, and incidence of CAMHS referral. RESULTS: Pupils experiencing more behavioural difficulties, had an increased incidence of CAMHS referral (adjusted hazard ratio 1.1, 95% confidence interval 1.0–1.2). However, pupils who reported higher health related quality of life had a lower incidence of CAMHS referral over the follow-up period (adjusted hazard hario 0.94, 95% confidence interval 0.9–0.98). CONCLUSION: Children and young people’s perception of their quality of life should be considered at the stages of a clinical needs assessment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12888-021-03364-2.